Análisis de los principales influencers en Ecuador en el sector youtubersSu interactividad y real influencia en YouTube - Guaman Córdova, Grace Isabel (2018)
Abstract:The technology a new model of business has allowed to create, the use of influential persons of the social networks or influencers. In YouTube they are known like youtubers and his level of scope and influence is so big that they can manage to gain million dollars for his recommendations. Therefore, with Fanpagkarma's help one tried to analyze 10 principal youtubers in Ecuador, his content, the way of being projected, if they use or not advertising and of what type, the most frequent brands and other characteristics that allowed to understand a bit more of this digital world. As result, there was obtained that Enchufetv and HipotesisdePoder are those who have more and fewer subscribers with 16693350 and 417325, respectively. In addition, that the content preferred by the fans is the comedy. Likewise, that of 10 YouTube's channels analyzed only two of them do not realize advertising and that some brands used by the Ecuadoran youtubers are: Güitig, adidas, Muscle Juice, Movistar, Tuenti, Shop.enchufe.com, Google and Flower shop Scarlet, Play Station, Samsung, between others.